Post-2008 Films: The Financial Crisis in Fictions and Documentaries - Juliette Feyel; Clémence Fourton (Angles)
The 2008 crisis has been represented in many fiction and documentary films. This paper analyses these representations in order to present the aesthetic and political characteristics of widely circulated narratives of the crisis. This paper analyses 8 films, starting with an overview, then a structural comparison of these films, isolating the common features of this sub-genre in terms of tropes, characterization and narrative strategy. The paper then assesses the films’ critical dimension against the complexity of their depiction of the 2008 neoliberal crisis and the space granted to anticapitalist voices. Both fictions and documentaries reveal a didactic dimension, but they differ as to their critical dimension. Fictions, with their brilliant casts and alluring dramatization, did well at making a dry topic both accessible and visually attractive, with the risk of glamorizing a topic of both ethical and ideological importance. Documentaries offer a much more critical view, especially when they address the crisis as a worldwide phenomenon revealing the shortcomings of neoliberalism, and when they display popular dissent directed at capitalism. These films armed their viewers with technical knowledge about finance, but for the most part did not encourage viewers to question capitalism as such.